Patterns of Debt Use in Small Businesses: A Non-Parametric Analysis - Chakraborty, Atreya; Mallick, Rajiv (Universiti Utara Malaysia, 2010)
This paper uses non-parametric techniques to examine patterns of debt use by small firms and how such patterns differ across firm categories. The methodological goal is to use the richness of the firm level data and allow convincing presentations with minimum of assumptions. The procedures used provide easily comprehendible graphical descriptions of the data. The procedures augment what can be discerned from descriptive statistics by accounting for differential weights and allowing for clustering that is a native feature of cross-sectional data. We also investigate how firms could benefit if credit availability improves. Though a model-based analysis would be required to provide a detailed analysis, our analysis suggests that greater credit availability will benefit all firms. Firms with low levels of equity will be better off as their credit constraints will be less binding, while firms with high levels of equity will benefit from acquiring more debt.